Development of an Online Shopping System for BinDawood - Mabrouk, Wafa; Nureize Arbaiy, (Applied Information Technology And Computer Science, 2023)
The bin Dawood online shopping system is a website that facilitates consumer purchases and sells electrical products, home furnishings, clothing, food, and fruits. The system is considered beneficial for online shopping and an excellent alternative to traditional shopping. During which the majority of customers avoid long lines and traffic. When a customer orders a product through the Website and it is delivered to the home in a timely manner while ensuring the product's quality, which is measured by the opinions of other customers, then the online shopping will be satisfied with customers. The online shopping platform for the Bin Dawood shop, which had been created using Visual Studio, could be distinguished by this particular facet of its design. It is expected that the system will provide a huge selection of products, save time and effort, and ensure that the items supplied are of high quality.